Alexandru Buzalic, Anthropos—Omul Paradigmele unui model antropologic integral [Anthropos—Man. Paradigms of an Integral Anthropological Model] Târgu-Lăpuş: Galaxia Gutenberg, 2022, 228 pp. - Dancák, Pavol (Philosophy and Canon Law, 2023)
Alexandru Buzalic, Anthropos – Omul. Paradigmele unui model antropologic integral [Anthropos - Man. Paradigms of an integral anthropological model]. Târgu-Lăpuş: Galaxia Gutenberg, 2022, 228 pp.